Effect of Water Hyacinth (Eichhornia crassipes) and Biochar on pH and Fe and Mn Concentrations in Acid Mine Drainage - Fitriyati Sholehati Albanjari; Ajidirman Ajidirman; Wiskandar Wiskandar (Rifa'Institute, 2026)
Introduction: Acid mine drainage (AMD) is a major environmental problem characterized by low pH and elevated heavy metals such as Fe and Mn that can contaminate aquatic ecosytems. Environmentally friendly treatment alternatives include water hyacinth (Eichhornia crassipes) for phytoremediation and biochar for metal adsorption and pH buffering Objective: To analyze the effects of water hyacinth and biochar on increasing pH and reducing Fe and Mn concentrations in AMD Method: An experimental study was conducted using combination treatments of water hyacinth and biochar at several dosage levels. Measured parameters included pH and Fe–Mn concentrations. Data were analyzed using ANOVA followed by Duncan’s New Multiple Range Test (DNMRT) at a 5% significance level. Results and Discussion: Water hyacinth did not significantly increase pH but significantly reduced Fe at 15 stems. Biochar significantly raised pH toward near-neutral conditions and reduced Fe and Mn, with the best performance at 20 g L⁻¹. Combined treatments were more effective than single treatments, increasing pH to 6.5–7.5 and achieving >99% Fe and Mn removal Conclusion: Water hyacinth–biochar combinations offer a promising, low-cost, and eco-friendly AMD treatment via synergistic phytoremediation and adsorption